Architecture and the Environment. Issue 1 (14th December 2018) - Hochhäusl, Sophie; Lange, Torsten
Abstract : These Field Notes, on the topic of Architecture and the Environment, elucidate how problems raised in the environmental humanities have informed architectural history, and in turn, what architectural history has to contribute to this emerging field. The short essays explore specific 'positions' in the overarching debate, identifying a radical return to critical theory and the embrace of the fundamentally transdisciplinary nature of environmental humanities and architectural history. While the positions advocate for a serious investigation of architects' texts and ideas on environmental issues, the collection also champions a broader engagement with Anthropocene questions and proposes to adopt the environment as an intellectual perspective from which to look upon the world.